2018
DOI: 10.1371/journal.pone.0197988
|View full text |Cite
|
Sign up to set email alerts
|

Increasing belief but issue fatigue: Changes in Australian Household Climate Change Segments between 2011 and 2016

Abstract: Using national Australian samples collected in 2011 (n = 1927) and 2016 (n = 2503), we identified six Australian household segments which we labelled Alarmed, Concerned, Cautious, Disengaged, Doubtful and Dismissive. Between the two periods, we found the proportion of households in the Alarmed and Concerned segments was stable; however there was a decrease (28% to 20%) in the proportion of households in the Doubtful and Dismissive segments and an increase (27% to 33%) in the Cautious and Disengaged segments. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…If authors used methods that facilitated transparent reporting and continued efforts, future research could take proposed segment solutions and apply them to their data for, say, another country or another time period. In climate change communication, the "Six Americas" solution (Maibach, Leiserowitz, Roser-Renouf, & Mertz, 2011) highlights this potential; researchers have applied it to other countries and periods (M. Morrison et al, 2013;Mark Morrison et al, 2018) and developed shorter scales (Chryst et al, 2018;Swim & Geiger, 2015). The continued efforts we see in science communication are be authors taking qualitative looks at specific clusters discovered in their previous studies (Kawamoto et al, 2013).…”
Section: Latent Class Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…If authors used methods that facilitated transparent reporting and continued efforts, future research could take proposed segment solutions and apply them to their data for, say, another country or another time period. In climate change communication, the "Six Americas" solution (Maibach, Leiserowitz, Roser-Renouf, & Mertz, 2011) highlights this potential; researchers have applied it to other countries and periods (M. Morrison et al, 2013;Mark Morrison et al, 2018) and developed shorter scales (Chryst et al, 2018;Swim & Geiger, 2015). The continued efforts we see in science communication are be authors taking qualitative looks at specific clusters discovered in their previous studies (Kawamoto et al, 2013).…”
Section: Latent Class Analysismentioning
confidence: 99%
“…This creates a situation where researchers have high quality data, can focus on a common topic and start using segmentation analyses by systematically varying national and temporal contexts. Segmentation analyses in climate change communication have already shown that proposed segmentation solutions of one country can be directly applied to another country (M. Morrison, Duncan, Sherley, & Parton, 2013), or tracked across time within the same country (Mark Morrison, Parton, & Hine, 2018). Science communication could mimic and even surpass such efforts.…”
mentioning
confidence: 99%
“…Effective management of collapsing ecosystems is essential for the ecological sustainability of the environment to support both people's health and livelihoods and whole ecosystem biodiversity. Managing physical environmental degradation is difficult and complex, and can only be successful when diverse segments of the community can be motivated to overcome issue fatigue and feelings of failure (Kerr, 2009; Morrison et al, 2018). Furthermore, in contrast to ecosystem change with a smooth collapse profile, abrupt change can come as a surprise because changes in feedbacks within ecosystems can go unnoticed (Crépin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As regards fatigue, the World Health Organization (WHO, 2020 ) published a report immediately after the beginning of the second wave as a response to EU Member States who were reporting that populations seemed to be highly fatigued and less compliant with the recommended protective measures. The WHO ( 2020 ) introduced the concept of “pandemic fatigue,” defined in line with previous studies (Masten & Motti-Stefanidi, 2020 ; Morrison et al, 2018 ) as a natural long-term response to the adversity caused by a pandemic whose main outcome is a demotivation in terms of engaging in recommended protective behaviors. “Pandemic fatigue” could also be interpreted as a sort of “societal burnout” (Queen & Harding, 2020 ), i.e.…”
Section: Introductionmentioning
confidence: 99%